Exploring Factors Influencing Repurchase Intention of Thai Cultural Design Cloth Products - Yoopetch, Chanin; Damrongmahasawat, Salinthip; Promsiri, Triyuth (Journal of Ecohumanism, 2024)
This study investigates the factors that influence the repurchase intention of young consumers towards cultural design cloth products, which encompass traditional attire and culturally themed clothing. Young consumers, known for their significant purchasing power, were the focus of this research. Drawing on the theory of planned behavior (TPB), this study examines the impact of attitude (ATT), subjective norms (SN), perceived behavioral control (PBC), and perceived risk (PR), on repurchase intention (RI) of cultural design cloth products. The study analyzed data using a sample of 523 young consumers using Structural Equation Modeling (SEM) and AMOS Version 20 software. The findings revealed that ATT exerts direct and positive influences on RI, while PR does not significantly affect RI. Additionally, five of the seven proposed hypotheses were supported. Moreover, this study extends the application of the TPB by exploring its mediating role between PBC, SN, PR, and ATT om RI of cultural products. Practitioners can leverage these insights to enhance repurchase activities within their businesses.